Diversity of toxin and non-toxin containing cyanobacterial mats of meltwater ponds on the Antarctic Peninsula: a pyrosequencing approach. Issue 5 (14th May 2014) - Kleinteich, J.; Hildebrand, F.; Wood, S.A.; Ciŕs, S.; Agha, R.; Quesada, A.; Pearce, D.A.; Convey, P.; K̈pper, F.C.; Dietrich, D.R.
Abstract: Despite their pivotal role as primary producers, there is little information as to the diversity and physiology of cyanobacteria in the meltwater ecosystems of polar regions. Thirty cyanobacterial mats from Adelaide Island, Antarctica were investigated using 16S rRNA gene pyrosequencing and automated ribosomal intergenic spacer analysis, and screened for cyanobacterial toxins using molecular and chemical approaches. A total of 274 operational taxonomic units (OTUs) were detected. The richness ranged between 8 and 33 cyanobacterial OTUs per sample, reflecting a high mat diversity. Leptolyngbya and Phormidium ( c . 55% and 37% of the OTUs per mat) were dominant. Cyanobacterial community composition was similar between mats, particularly those obtained from closely adjacent locations. The cyanotoxin microcystin was detected in 26 of 27 mats (10–300 ng g -1 organic mass), while cylindrospermopsin, detected for the first time in Antarctica, was present in 21 of 30 mats (2–156 ng g -1 organic mass). The latter was confirmed via liquid chromatography-mass spectrometry and by the presence of the cyrAB and cyrJ genes. This study demonstrates the usefulness of pyrosequencing for characterizing diverse cyanobacterial communities, and confirms that cyanobacteria from extreme environments produce a similar range of cyanotoxins as their temperate counterparts.